Household level economic and nutritional impacts of market-oriented dairy production in the Ethiopian highlands - Ahmed, M.M.; Jabbar, M.A.; Ehui, Simeon K. (United Nations University, 2000)
Previous farm-level studies have shown that adopting improved feeding and management strategies improves livestock productivity and, in particular, increases the milk production and income of resource poor smallholder mixed-crop and livestock farmers. This paper analyses the impact of the introduction of crossbred cow and improved feeding and management technologies in the Ethiopian highlands in terms of direct changes in house hold income, patterns of food and non-food expenditure, and caloric intake. Using a recursive econometric model that takes into account the seasonal variability of consumption patterns, the analysis indicates a positive relationship between household income and adoption of the improved dairy technologies. The incremental increase in household income translates directly into higher expenditure on food and non-food items. Caloric intake is also positively related to adoption of crossbred cows and improved feed technologies. This indicates the significant role that improved smallholder livestock technologies can play in improving food security and nutrition as well as alleviating poverty.